High-temperature-resistant wave-absorbing honeycomb, preparation method and application thereof
Patent Information
- Application Number
- CN202611252652.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-27
AI Technical Summary
然而,随着5G高频电路、大功率雷达等高功率电气设备的快速发展,传统浸渍型吸波蜂窝难以满足大于250℃的使用条件;一方面,芳纶复合纸内部的多孔结构及树脂非晶相主导了热传导路径,其内部无序的纤维-树脂界面与残留孔隙导致声子散射加剧,阻碍了热流的定向传递,导致芳纶纸本身的导热系数较低(0.206W·(m·K)-1),易引发局部热量富集;另一方面,传统工艺依赖涂覆吸波浆料来实现电磁响应,但这些化学浆料的耐温上限通常不超过180℃,在局部高温下极易发生降解或脱落
[0015]1.本发明采用激光诱导技术在芳纶纸上原位刻划出具有电磁功能性的图案,以物理结构的电磁响应替代了传统的浸渍化学吸波浆料方法。解决了传统吸波涂层在高温环境下的降解与脱落风险,使得制备的蜂窝材料在高温条件下仍能保持稳定、不衰减的吸波性能。
Smart Images

Figure CN122976117A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of aramid paper honeycomb technology, specifically to a high-temperature resistant microwave absorbing honeycomb, its preparation method, and its application. Background Technology
[0002] Currently, aramid paper honeycomb is widely used as a matrix for preparing microwave absorbing honeycomb materials due to its light weight and high strength, and it has important applications in electromagnetic shielding, radar radomes and other fields.
[0003] Traditional microwave-absorbing aramid honeycomb structures are mostly prepared by impregnating the matrix with microwave-absorbing slurry (such as phenolic resin or polyurethane resin). However, with the rapid development of high-power electrical equipment such as 5G high-frequency circuits and high-power radar, traditional impregnated microwave-absorbing honeycomb structures are unable to meet the operating conditions of temperatures exceeding 250°C. On the one hand, the porous structure and amorphous phase of the resin within the aramid composite paper dominate the heat conduction path. The disordered fiber-resin interface and residual pores within the paper intensify phonon scattering, hindering the directional transfer of heat flow, resulting in a low thermal conductivity of the aramid paper itself (0.206 W·(m·K)). -1 On the one hand, it can easily lead to local heat accumulation; on the other hand, traditional processes rely on coating with microwave absorbing slurry to achieve electromagnetic response, but the upper limit of the temperature resistance of these chemical slurries is usually no more than 180°C, and they are very easy to degrade or fall off under local high temperature.
[0004] Therefore, how to reconstruct the heat conduction path of aramid composite materials and achieve stable electromagnetic response while abandoning heat-sensitive absorbing pastes is an urgent problem to be solved in current high-power equipment absorbing honeycomb materials. Summary of the Invention
[0005] The main objective of this invention is to provide a method for preparing a high-temperature resistant microwave absorbing honeycomb to solve the aforementioned technical problems. The method for preparing a high-temperature resistant microwave absorbing honeycomb provided by this invention includes the following steps: S1. Dry and flatten the aramid paper; laser-etch the aramid paper by adjusting the laser process parameters to etch electromagnetic functional patterns on the surface of the aramid paper; place the aramid paper with the etched electromagnetic functional patterns in an oven to dry in order to remove the moisture from the surface of the aramid paper. S2. A thin film is deposited on the surface of aramid paper using magnetron sputtering to obtain aramid composite paper with a thin film deposited on the surface; S3. Apply node adhesive to the surface of the aramid composite paper and stack the paper in a staggered overlapping manner; S4. Press the stacked aramid composite paper to obtain aramid paper blocks; S5. Stretch and shape the aramid paper block to obtain a semi-finished honeycomb. S6. Impregnate the semi-finished honeycomb in a high-temperature resistant resin matrix and pre-cure it; S7. Repeat S6 until the density of the semi-finished honeycomb reaches the preset target density, then perform final curing to obtain the high-temperature resistant absorbing honeycomb.
[0006] Furthermore, in S1, the thickness of the aramid paper is 40~80μm; the laser marking process parameters are: laser power of 10~24W and laser speed of 10~20m / s.
[0007] Furthermore, in S2, the thin film is an aluminum nitride thin film.
[0008] Furthermore, the thin film in S2 is a boron nitride thin film. The specific process steps of S2 are as follows: a boron nitride target with a purity of 99.99% is installed in the sputtering chamber of a magnetron sputtering equipment, and aramid paper with an electromagnetic functional pattern is fixed on a rotating substrate stage; the cavity is evacuated to 10... -4 At Pa, argon and nitrogen are simultaneously introduced into the cavity, with an argon to nitrogen flow rate ratio of (0.1~0.3):1 and an argon flow rate of 50~70 sccm. Under the conditions of sputtering power of 90~280W, substrate bias voltage of -120~-320V, sputtering pressure of 0.5~2.0Pa, distance between aramid paper and sputtering target of 6~15cm, and substrate temperature of 150~250℃, sputtering deposition is carried out for 30~180min.
[0009] Furthermore, in S3, the joint adhesive is a mixture of epoxy resin and ethyl acetate, or a mixture of polyimide resin and ethyl acetate; And / or, in S4, the pressing conditions are: hot pressing for 4 to 10 hours at a temperature of 160~240℃ and a pressure of 0.5~1.2MPa.
[0010] Furthermore, in step S5, the stretching and setting conditions are: stretching rate of 60~130mm / min, setting temperature of 240~280℃, and setting time of 4~8 hours.
[0011] Furthermore, in step S6, the high-temperature resistant resin matrix is one or more of bismaleimide resin or phenolic resin; And / or, in S7, the preset target density is 32 to 144 kg / m³.
[0012] Furthermore, when the resin is bismaleimide resin, the pre-curing conditions in S6 are: curing at a curing temperature of 180~250℃ for 0.5~4 hours; the final curing conditions in S7 are: curing at a curing temperature of 180~250℃ for 4~9 hours.
[0013] The present invention also provides an absorbing honeycomb, which is prepared by the aforementioned preparation method.
[0014] The present invention also discloses the application of a microwave absorbing cell in electrical equipment, including 5G communication equipment or radar antenna covers. The microwave absorbing cell of the present invention can be applied in high-temperature scenarios of 250°C, meeting the usage requirements of high-power electrical equipment.
[0015] 1. This invention employs laser-induced technology to in-situ etch electromagnetically functional patterns onto aramid paper, replacing the traditional method of impregnating chemical absorbing slurries with the electromagnetic response of the physical structure. This solves the risk of degradation and peeling of traditional absorbing coatings under high-temperature environments, enabling the prepared honeycomb material to maintain stable and undiminished absorbing performance even at high temperatures.
[0016] 2. To address the issue of low thermal conductivity in aramid composite paper, this invention deposits an insulating and highly thermally conductive thin film (such as aluminum nitride or boron nitride film) on the patterned surface with electromagnetic functionality. This allows for rapid conduction and diffusion of heat from the external environment and from wave absorption, preventing the formation of localized hot spots and thus improving the heat dissipation capacity and overall thermal stability of the aramid paper itself.
[0017] 3. The surface-deposited thin film material has excellent electromagnetic wave transmittance. Electromagnetic waves in the microwave band can penetrate the thin film layer and directly act on the resonant units in the underlying pattern. The surface thermally conductive thin film does not interfere with the wave absorption function of the underlying layer. At the same time, the thin film acts as a physical protective layer to isolate the underlying pattern from the external environment, reducing the risk of oxidation of the pattern at high temperatures.
[0018] 3. This invention uses a high-temperature resistant resin matrix (such as bismaleimide resin) for repeated impregnation and final high-temperature curing, so that the resulting absorbing honeycomb exhibits a significantly lower degree of planar compressive strength decay after a 250°C high-temperature test than traditional impregnated honeycomb. It possesses excellent high-temperature resistance and structural stability, and can meet the application requirements of high-power electrical equipment such as 5G communication equipment and radar radomes in extreme thermodynamic environments. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of an aramid paper structure with electromagnetic functional patterns in an embodiment of the present invention; Figure 2 This is a schematic diagram of the paper stacking structure in an embodiment of the present invention; The figure shows: 1. Aramid paper; 11. Electromagnetic functional pattern; 12. Film; 13. Node adhesive. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply.
[0021] like Figure 1 The diagram shows a schematic of an aramid paper structure with electromagnetic functional patterns. The structure includes aramid paper 1, the surface of which has electromagnetic functional patterns 11, and a thin film 12 (such as a BN film or an AlN film layer) is deposited on the electromagnetic functional patterns 11 and the surface of the aramid paper 1. A node adhesive 13 is coated on a specific area of the surface of the thin film 12.
[0022] like Figure 2 As shown, this is a schematic diagram of the paper stacking structure. Multiple aramid composite papers with thin films 12 deposited on their surfaces are stacked in a staggered manner with the joint adhesive 13 staggered.
[0023] The present invention discloses a method for preparing a high-temperature resistant absorbing honeycomb, comprising the following steps: S1: Dry aramid paper with a thickness of 40~80μm in an 80℃ oven for 4~6h, and then flatten it; under air conditions, laser scribing is performed on the aramid paper by adjusting the laser process parameters to scribing electromagnetic functional patterns. The laser process parameters are: laser power 10~24W, laser speed 10~20m / s; place the aramid paper with the scribed electromagnetic functional patterns in an 80°C oven for 4~6h to remove the moisture from the paper surface.
[0024] S2: A thin film is deposited on the surface of aramid paper with etched electromagnetic functional patterns using magnetron sputtering. Taking the deposition of boron nitride (BN) thin film as an example, a BN target with a purity of 99.99% is installed in the sputtering chamber of the magnetron sputtering equipment. The pretreated aramid paper is fixed on a rotating substrate stage and placed into a vacuum chamber; the chamber is evacuated to 10⁻⁻⁻⁶. 4 A mixture of argon and nitrogen gas is simultaneously introduced into the cavity at a flow rate ratio of (0.1~0.3):1, with an argon flow rate of 50~70 sccm. Under the conditions of sputtering power of 90~280W, substrate bias voltage of -120~-320V, sputtering pressure of 0.5~2.0Pa, distance between aramid paper and sputtering target of 6~15cm, and substrate temperature of 150~250℃, aramid composite paper with a BN thin film on the surface is obtained by sputtering deposition on the surface of aramid paper for 30~180min.
[0025] In this step, the thin film 12 serves as a continuous layer, covering the surface of the aramid paper 1 and the electromagnetic functional pattern 11. The material of the thin film 12 can be aluminum nitride or boron nitride, possessing insulation and wave transmission characteristics. Electromagnetic waves in the microwave frequency band can penetrate the thin film 12 and act on the underlying electromagnetic functional pattern 11, where the resonant units within the pattern achieve absorption and dissipation of the electromagnetic waves.
[0026] Furthermore, the thin film 12 forms a continuous heat conduction path on the surface of the electromagnetic functional pattern 11, which is used to conduct and diffuse external heat generated during equipment operation, as well as heat converted from electromagnetic waves absorbed by the underlying pattern, thereby suppressing the formation of local hot spots inside the material. Simultaneously, the thin film 12 acts as a physical protective layer, isolating the underlying pattern from the external environment to reduce the risk of oxidation or peeling of the pattern under high-temperature conditions (for example, the oxidation temperature of boron nitride in atmospheric conditions is 1300°C). This structure, through its layered design, achieves a physical separation of wave transmission and absorption, and thermal conduction and electromagnetic functions, enabling the manufactured material to meet the wave absorption and heat dissipation performance requirements of high-power electrical equipment.
[0027] S3: Apply adhesive to the aramid composite paper using a joint adhesive. After applying the adhesive, stack the paper according to the required dimensions in the width direction using a staggered stacking method. The joint adhesive is a mixture of epoxy resin or polyimide resin and ethyl acetate.
[0028] The staggered overlapping method in this step is shown in Figure 2, where the positions of the adhesive nodes on the two adjacent layers of aramid paper are staggered.
[0029] S4: Press the aramid composite paper after stacking to obtain aramid paper blocks; the pressing conditions are: hot pressing for 4 to 10 hours at a temperature of 160~240℃ and a pressure of 0.5~1.2MPa.
[0030] S5: Stretch and shape the aramid paper block after pressing to obtain a semi-finished honeycomb; the stretching rate is 60~130mm / min, and the shaping is carried out at 240~280°C for 4~8 hours.
[0031] S6: The semi-finished honeycomb is impregnated and pre-cured in resin; the resin is one or more of bismaleimide resin or phenolic resin. When bismaleimide resin is selected, it is pre-cured at a curing temperature of 180~250°C for 0.5~4 hours.
[0032] S7: Repeat step S6 until the honeycomb density reaches the preset target density of 32~144 kg / m³, then perform final curing to obtain the high-temperature resistant microwave absorbing honeycomb. When bismaleimide resin is used, cure at a curing temperature of 180~250℃ for 4~9 hours; when phenolic resin is used, cure at a curing temperature of 160~180℃ for 5~8 hours.
[0033] To further demonstrate the technical effects of the present invention, the following embodiments and comparative examples are provided.
[0034] Example 1
[0035] Aramid paper with a thickness of 80μm and model number YT-836 was used. The aramid paper was dried in an oven at 80℃ for 4 hours and then flattened. Electromagnetic functional patterns were laser-etched onto aramid paper under air conditions by adjusting the laser process parameters, with a laser power of 12W and a laser speed of 15m / s. Aramid paper with engraved electromagnetic functional patterns was placed in an 80℃ oven and dried for 6 hours to remove surface moisture. The BN target (99.99% purity) is installed in the sputtering chamber of the magnetron sputtering equipment, and the aramid paper with electromagnetic functional patterns is fixed on the rotating substrate stage of the magnetron sputtering and placed into the vacuum chamber. Evacuate the cavity to 10⁻ 4 Pa, and then a mixture of argon and nitrogen gas is simultaneously introduced into the cavity. The purity of the argon gas is 99.999%, the purity of the nitrogen gas is 99.999%, the flow rate ratio of argon to nitrogen is 0.2:1, the argon flow rate is 50 sccm, the sputtering power is 200W, the substrate bias voltage is -200V, the sputtering pressure is 1.3Pa, the distance between the aramid paper and the sputtering target is 12cm, and the substrate temperature is 180°C. A BN film is sputtered and deposited on the surface of the aramid paper for 180min to obtain aramid paper with a BN film on the surface. The mixture of polyimide resin and ethyl acetate is coated onto aramid paper with a BN film, with a coating width of 2.75 mm, and the paper is stacked alternately. The aramid paper after stacking is pressed together by hot pressing at 180°C and 0.8MPa. The aramid paper block after hot pressing is stretched and shaped using a honeycomb stretching machine at a stretching rate of 75 mm / min to obtain a semi-finished honeycomb. The semi-finished honeycomb was cured at 270℃ for 5 hours to set its shape. The set semi-finished honeycomb was then impregnated and pre-cured in bismaleimide resin at 180℃ for 2 hours. If the target density was not reached, the impregnation was repeated until the target density of 64 kg / m³ was reached. Finally, the honeycomb was cured at 250℃ for 6 hours to obtain the honeycomb.
[0036] Example 2: The adhesive application width is 1.83 mm, and everything else is the same as in Example 1.
[0037] Comparative Example 1: Aramid paper with a thickness of 0.08mm and model number YT-836 was coated with a mixture of polyimide resin and ethyl acetate, with a coating width of 2.75mm, and the paper was stacked alternately. The aramid paper after stacking is pressed together by hot pressing at 180℃ and 0.8MPa. The aramid paper block after hot pressing is stretched and shaped using a honeycomb stretching machine at a stretching rate of 75 mm / min to obtain a semi-finished honeycomb. The semi-finished honeycomb was cured at 270℃ for 5 hours to set its shape. The set semi-finished honeycomb was then impregnated and pre-cured in bismaleimide resin at 180℃ for 2 hours. If the target density was not reached, the impregnation was repeated until the target density of 64 kg / m³ was reached. Finally, the honeycomb was cured at 250℃ for 6 hours to obtain the honeycomb.
[0038] Comparative Example 2: The adhesive application width was 1.83 mm, and everything else was the same as Comparative Example 1.
[0039] Comparative Example 3: White honeycomb with a density of 64 kg / m³ was impregnated in an epoxy resin or polyurethane resin impregnation solution containing at least one microwave absorbing agent (carbon black, carbon nanotubes, or carbonyl iron powder). The curing temperature was 70°C for 2 hours to obtain a microwave absorbing honeycomb produced by the impregnation process. The relatively low curing temperature of 70°C was set here because traditional microwave absorbing slurries and resin systems cannot withstand temperatures above 200°C; otherwise, carbonization degradation or large-area detachment of the microwave absorbing agent would easily occur, leading to preparation failure.
[0040] The honeycomb cells prepared in the above embodiments and comparative examples were placed at 250°C for 168 hours. The following tests were performed before and after placement, and the test results are shown in Table 1: 1. The reflectivity was tested according to the national military standard "GJB2038A-2011 Test Method for Reflectivity of Radar Absorbing Materials"; 2. Perform plane compression tests according to the standard "ASTM C365 Test Method for Planar Compression Performance of Sandwich Cores".
[0041] Table 1 Comparison of reflectivity and planar compressive strength test results before and after high-temperature test
[0042] According to the data in Table 1, after high-temperature testing, the planar compressive strength of Examples 1 and 2 decreased significantly less than that of Comparative Examples 1, 2, and 3, indicating that the present invention can effectively reduce the degree of mechanical property degradation at high temperatures. Meanwhile, the reflectivity of Examples 1 and 2 did not decrease significantly after high-temperature testing, while the absorption degradation of Comparative Example 3 (traditional impregnation absorbing slurry process) was extremely high. The experimental data show that the honeycomb absorbing performance prepared by the present invention does not change with high temperature, has excellent high-temperature resistance and structural stability, can be applied to high-power electrical equipment, and meets the usage requirements in high-temperature scenarios of 250℃.
[0043] Based on the preferred embodiments of the present invention described above, and through the above description, those skilled in the art can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the contents of the specification.
Claims
1. A method for preparing a high-temperature resistant absorbing honeycomb, characterized in that, Includes the following steps: S1. Dry and flatten the aramid paper; laser-etch the aramid paper by adjusting the laser process parameters to etch electromagnetic functional patterns on the surface of the aramid paper; place the aramid paper with the etched electromagnetic functional patterns in an oven to dry in order to remove the moisture from the surface of the aramid paper. S2. A thin film is deposited on the surface of aramid paper using magnetron sputtering to obtain aramid composite paper with a thin film deposited on the surface; S3. Apply node adhesive to the surface of the aramid composite paper and stack the paper in a staggered overlapping manner; S4. Press the stacked aramid composite paper to obtain aramid paper blocks; S5. Stretch and shape the aramid paper block to obtain a semi-finished honeycomb. S6. Impregnate the semi-finished honeycomb in a high-temperature resistant resin matrix and pre-cure it; S7. Repeat S6 until the density of the semi-finished honeycomb reaches the preset target density, then perform final curing to obtain the high-temperature resistant absorbing honeycomb.
2. The preparation method according to claim 1, characterized in that, In S1, the thickness of the aramid paper is 40~80μm; the laser marking process parameters are: laser power of 10~24W and laser speed of 10~20m / s.
3. The preparation method according to claim 1, characterized in that, In S2, the thin film is an aluminum nitride thin film.
4. The preparation method according to claim 1, characterized in that, The thin film in S2 is a boron nitride thin film, and the specific process steps of S2 are as follows: A boron nitride target with a purity of 99.99% was installed in the sputtering chamber of a magnetron sputtering equipment, and aramid paper with an electromagnetic functional pattern was fixed on a rotating substrate stage; the chamber was evacuated to 10... -4 At Pa, argon and nitrogen are simultaneously introduced into the cavity, with an argon to nitrogen flow rate ratio of (0.1~0.3):1 and an argon flow rate of 50~70 sccm. Under the conditions of sputtering power of 90~280W, substrate bias voltage of -120~-320V, sputtering pressure of 0.5~2.0Pa, distance between aramid paper and sputtering target of 6~15cm, and substrate temperature of 150~250℃, sputtering deposition is carried out for 30~180min.
5. The preparation method according to any one of claims 1 to 4, characterized in that, In S3, the joint adhesive is a mixture of epoxy resin and ethyl acetate, or a mixture of polyimide resin and ethyl acetate; And / or, in S4, the pressing conditions are: hot pressing for 4 to 10 hours at a temperature of 160~240℃ and a pressure of 0.5~1.2MPa.
6. The preparation method according to any one of claims 1 to 4, characterized in that, In step S5, the stretching and setting conditions are: stretching rate of 60~130mm / min, setting temperature of 240~280℃, and setting time of 4~8 hours.
7. The preparation method according to any one of claims 1 to 4, characterized in that, In step S6, the high-temperature resistant resin matrix is one or more of bismaleimide resin or phenolic resin; And / or, in S7, the preset target density is 32 to 144 kg / m³.
8. The preparation method according to claim 7, characterized in that, When the resin is bismaleimide resin, the pre-curing conditions in S6 are: curing at a curing temperature of 180~250℃ for 0.5~4 hours; the final curing conditions in S7 are: curing at a curing temperature of 180~250℃ for 4~9 hours.
9. A high-temperature resistant absorbing honeycomb, characterized in that, Prepared by the preparation method described in any one of claims 1 to 8.
10. The application of the high-temperature absorbing honeycomb as described in claim 9 in electrical equipment, characterized in that, Electrical equipment includes 5G communication equipment or radar antenna covers.